Tafsir Mushafi Tentang Fonologi dan Ragam Modelnya : (Perbedaan Vokal aalam Quran dalam Pandangan Fonetik Modern) - Husain Nasir; Abubakar, Achmad; Galib, Muhammad; Kasim, Amrah; Mahfudz, Muhsin (ELOQUENCE : Journal of Foreign Language, 2023)
Background: In the science of Qiraat, the problem of vowel reading on letters and words in the Qur'an is still much that has not been revealed, both from the aspect of classical and modern scholarly opinions. Purpose: This study aims to describe and introduce several rules about the process of occurrence of vowel a/i/u in certain words and verses, which are caused by the presence of letters, hamzah, sukun, and ishmam, including exploring new ways of analyzing the phonology of modern Arabic vowels based on standard generative theory. Method: This research is literature research. Primary data sources were obtained by al-Našr fi al-Qirā'at al-Islāmiyyah, and several verses of the Qur'an for comparison. Secondary data sources are literature, both in the form of books, journals, and research results related to phonology. Data collection is carried out by documentation techniques, listening, and recording. Data analysis techniques use open coding, then analyzed descriptively using grounded theory. Results and Discussion: This study informs about the rule that the variety of vowel punctuation on some verbs in the Qur'an will change according to the readings attributed to the ten Qira'at. The Vowel sign emphasizes the reading of dhamma/kasrah). The emphasis mark on nouns requires the insertion of dhamma while on verbs and insertion of kasrah. The round distinguishing mark (sifr) is important in turning kasrah into dhamma. Both Kasrah and dhamma have the property of 'Al, but some of them are distinguished by round marks on dhamma and square marks on kasrah. The Vowel sign for classical scholars indicates that the kasrah from the letter "waw" in the verb "qul" moved to the letter "qaf" after hadzf dhamma, then "waw" changed to "ya" to correspond to the kasrah in front of it. Modern linguists believe that the dhamma of the letter "qaf" can be changed to Kasrah and then "waw" removed, so that the existence of the two kasrahs is merged and becomes a long shaddah Conclusions and Implications: The differences and changes in vowels in phonetics cannot be separated from the debate that exists between classical and modern scholars. This indicates that the problem of qira'at is closely related to diacritical marks that are icons of producing sounds with various characters. This research has implications that having to study Qur'anic verses from a Vowel aspect will require us to see how scholars used to read so that the sounds produced are not only one variant but have a variety of very detailed and interesting reasons to be studied based on modern linguistic theory.